2007
DOI: 10.1128/jb.00129-07
|View full text |Cite
|
Sign up to set email alerts
|

Roles of rapH and rapG in Positive Regulation of Rapamycin Biosynthesis in Streptomyces hygroscopicus

Abstract: Rapamycin is an important macrocyclic polyketide produced by Streptomyces hygroscopicus and showing immunosuppressive, antifungal, and antitumor activities as well as displaying anti-inflammatory and neuroregenerative properties. The immense pharmacological potential of rapamycin has led to the production of an array of analogues, including through genetic engineering of the rapamycin biosynthetic gene cluster. This cluster contains several putative regulatory genes. Based on DNA sequence analysis, the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 46 publications
3
65
1
2
Order By: Relevance
“…Together, these data suggest that BldD positively regulates the ery genes. However, because the mutation left some synthesis of erythromycin intact, it differs from deletions of activators in many streptomycetes that abolish the production of an antibiotic completely (3,23). Our observations more closely resemble the case of S. noursei, in which a strain with a deletion of a nystatin synthesis regulator still produced some antibiotic (24).…”
Section: Recombinant Bldd Binds To Ery Promoters and To Its Own Promosupporting
confidence: 58%
“…Together, these data suggest that BldD positively regulates the ery genes. However, because the mutation left some synthesis of erythromycin intact, it differs from deletions of activators in many streptomycetes that abolish the production of an antibiotic completely (3,23). Our observations more closely resemble the case of S. noursei, in which a strain with a deletion of a nystatin synthesis regulator still produced some antibiotic (24).…”
Section: Recombinant Bldd Binds To Ery Promoters and To Its Own Promosupporting
confidence: 58%
“…60 Recently, the Biotica group showed that RapH and RapG have important roles as positive regulators in rapamycin biosynthesis. 23 Overexpression of rapH and rapG under the control of the ActII-ORF4/PactI activator/promoter in S. hygroscopicus enhanced the production of rapamycin by approximately 27-55% and 20-32%, respectively. The ActII-ORF4/PactI expression system, which is a robust activator/promoter expression system that has been widely used for many actinomycetes, including S. hygroscopicus, was used to minimize the potential self-regulatory interference of RapH and/or RapG and other endogenous regulatory genes.…”
Section: Biological Activities Of Rapamycin and Its Analogsmentioning
confidence: 99%
“…For example, the Biotica group (Cambridge, UK) revealed various positive regulatory elements in rapamycin biosynthesis, 23 the Wyeth group (Madison, NJ, USA) modified the pipecolate ring of rapamycin and Leadlay and coworkers 24 synthesized several rapamycin analogs with modifications to the cyclohexyl moiety through genetic engineering and mutasynthesis. Recently, Graziani 25 provided a review article on the advances in the field of rapamycin biosynthesis and neuroprotective activity of rapamycin analogs.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This cluster is not associated with any metabolite production and is found to be poorly expressed. These workers expressed this cryptic gene cluster using large ATP-binding regulator of the LuxR family (LAL) protein, the members of which are known to be activator of pikromycin [3] and rapamycin [4]. NMR analysis of the expressed product suggested that the product is a novel macrolide which was named stambomycin.…”
mentioning
confidence: 99%